2010
DOI: 10.1148/radiol.09090102
|View full text |Cite
|
Sign up to set email alerts
|

Breast Arterial Calcifications on Mammograms Do Not Predict Coronary Heart Disease at Coronary Angiography

Abstract: The authors did not observe a correlation between BAC and coronary angiography-detected CHD, even when CHD severity was considered. On the basis of these results, caution should be exercised when using screening mammography-detected BAC to identify patients with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 21 publications
3
33
0
1
Order By: Relevance
“…16 Only 4 of 19 studies did not show an association between BAC and CAD, 10,12,13,16 13 of 19 (68%) studies showed a clear cut, statistically significant association, and 2 of 19 studies showed significant association only when obstructive CAD (≥50% stenosis) was considered. 11,14 Obstructive CAD was generally defined as ≥50% coronary artery stenosis, except by Sarrafzadegann et al, 16 who used ≥50% stenosis in left main coronary artery and/or ≥75% stenosis in other epicardial arteries as the definition of obstructive CAD. There was 1 prospective cohort study, 7 2 retrospective cohort studies, 8,9 9 case-control studies with CAD, 1018 1 case-control study with BAC, 19 and 7 cross-sectional (prevalence) studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Only 4 of 19 studies did not show an association between BAC and CAD, 10,12,13,16 13 of 19 (68%) studies showed a clear cut, statistically significant association, and 2 of 19 studies showed significant association only when obstructive CAD (≥50% stenosis) was considered. 11,14 Obstructive CAD was generally defined as ≥50% coronary artery stenosis, except by Sarrafzadegann et al, 16 who used ≥50% stenosis in left main coronary artery and/or ≥75% stenosis in other epicardial arteries as the definition of obstructive CAD. There was 1 prospective cohort study, 7 2 retrospective cohort studies, 8,9 9 case-control studies with CAD, 1018 1 case-control study with BAC, 19 and 7 cross-sectional (prevalence) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Please note that some of the crude ORs and P values shown in Table 1 may not be quoted in full text articles of the respective studies, because we calculated these values by a repeat analysis of data based on the information provided in the methods and results sections of each study (see Statistical Analyses under Methods section for details). In addition, we were able to access the full-study database of Zgheib et al, 11 because this study was conducted at our institution (Staten Island University Hospital).…”
Section: Resultsmentioning
confidence: 99%
“…In their study, BAC was inversely related to smoking, a finding that has been previously shown as another indication of BAC lacking an inflammatory effect (9). Similarly, Zgheib (18) and Sarrafzadegann (19) did not find a statistically significant relation between angiographically detected coronary heart disease and BAC.…”
Section: Discussionmentioning
confidence: 92%
“…Zgheib et al found no correlation between BAC and coronary artery disease (CAD), even when CAD severity was considered (13). Penugonda et al also demonstrated that BAC was not positively associated with CAD or acute cardiovascular event (12).…”
Section: Discussion:-mentioning
confidence: 99%
“…Several investigations have suggested BAC as a marker of arterial disease that could be associated with increased risk of cardiac events (9,10). On the other hand, other studies have reported no significant association between BAC and cardiovascular diseases (11,12,13).…”
Section: Introduction:-mentioning
confidence: 99%